The Amish wife : unraveling the lies, secrets, and conspiracy that let a killer go free - Olsen, Gregg (Thomas & Mercer, 2024)
"In 1977, in an Ohio Amish community, pregnant wife and mother Ida Stutzman perished during a barn fire. The coroner's report: natural causes. Ida's husband, Eli, was never considered a suspect. But when he eventually rejected the faith and took his son, Danny, with him, murder followed. What really happened to Ida? The dubious circumstances of the tragic blaze were willfully ignored and Eli's shifting narratives disregarded. Could Eli's subsequent cross-country journey of death--including that of his own son--have been prevented if just one person came forward with what they knew about the real Eli Stutzman? The questions haunted Gregg Olsen and Ida's brother Daniel Gingerich for decades. At Daniel's urging, Olsen now returns to Amish Country and to Eli's crimes first exposed in Olsen's Abandoned Prayers, one of which has remained a mystery until now. With the help of aging witnesses and shocking long-buried letters, Olsen finally uncovers the disturbing truth--about Ida's murder and the conspiracy of silence and secrets that kept it hidden for forty-five years"--